Atorvastatin inhibits the proliferation of MKN45-derived gastric cancer stem cells in a mevalonate pathway-independent manner - Choi, Ye Seul; Cho, Hee Jeong; Jung, Hye Jin (The Korean journal of physiology & pharmacology, 2022)
Gastric cancer stem cells (GCSCs) are a major cause of radioresistance and chemoresistance in gastric cancer (GC). Therefore, targeting GCSCs is regarded as a powerful strategy for the effective treatment of GC. Atorvastatin is a widely prescribed cholesterol-lowering drug that inhibits 3-hydroxy-3-methylglutaryl-coenzyme A reductase, a rate-limiting enzyme in the mevalonate pathway. The anticancer activity of atorvastatin, a repurposed drug, is being investigated; however, its therapeutic effect and molecular mechanism of action against GCSCs remain unknown. In this study, we evaluated the anticancer effects of atorvastatin on MKN45-derived GCSCs. Atorvastatin significantly inhibited the proliferative and tumorsphere-forming abilities of MKN45 GCSCs in a mevalonate pathway-independent manner. Atorvastatin induced cell cycle arrest at the G0/G1 phase and promoted apoptosis by activating the caspase cascade. Furthermore, atorvastatin exerted an antiproliferative effect against MKN45 GCSCs by inhibiting the expression of cancer stemness markers, such as CD133, CD44, integrin α6, aldehyde dehydrogenase 1A1, Oct4, Sox2, and Nanog, through the downregulation of β-catenin, signal transducer and activator of transcription 3, and protein kinase B activities. Additionally, the combined treatment of atorvastatin and sorafenib, a multi-kinase targeted anticancer drug, synergistically suppressed not only the proliferation and tumorsphere formation of MKN45 GCSCs but also the in vivo tumor growth in a chick chorioallantoic membrane model implanted with MKN45 GCSCs. These findings suggest that atorvastatin can therapeutically eliminate GCSCs.Gastric cancer stem cells (GCSCs) are a major cause of radioresistance and chemoresistance in gastric cancer (GC). Therefore, targeting GCSCs is regarded as a powerful strategy for the effective treatment of GC. Atorvastatin is a widely prescribed cholesterol-lowering drug that inhibits 3-hydroxy-3-methylglutaryl-coenzyme A reductase, a rate-limiting enzyme in the mevalonate pathway. The anticancer activity of atorvastatin, a repurposed drug, is being investigated; however, its therapeutic effect and molecular mechanism of action against GCSCs remain unknown. In this study, we evaluated the anticancer effects of atorvastatin on MKN45-derived GCSCs. Atorvastatin significantly inhibited the proliferative and tumorsphere-forming abilities of MKN45 GCSCs in a mevalonate pathway-independent manner. Atorvastatin induced cell cycle arrest at the G0/G1 phase and promoted apoptosis by activating the caspase cascade. Furthermore, atorvastatin exerted an antiproliferative effect against MKN45 GCSCs by inhibiting the expression of cancer stemness markers, such as CD133, CD44, integrin α6, aldehyde dehydrogenase 1A1, Oct4, Sox2, and Nanog, through the downregulation of β-catenin, signal transducer and activator of transcription 3, and protein kinase B activities. Additionally, the combined treatment of atorvastatin and sorafenib, a multi-kinase targeted anticancer drug, synergistically suppressed not only the proliferation and tumorsphere formation of MKN45 GCSCs but also the in vivo tumor growth in a chick chorioallantoic membrane model implanted with MKN45 GCSCs. These findings suggest that atorvastatin can therapeutically eliminate GCSCs.